Pythium insidiosum: an emerging pathogen that is easily misdiagnosed and given treatment as a fungus - Hu, Liuyang; Huang, Xiulu; Yee, Ngan Hung; Meng, Huixia; Jiang, Li; Liang, Liang; Chen, Xingchun (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundPythium insidiosum (P. insidiosum) is the causative agent of pythiosis, an infectious disease with a high morbidity and fatality rate. Pythiosis cases have increased dramatically during the past ten years, particularly in tropical and subtropical areas. Sadly, microbiologists and medical professionals know very little about pythiosis, and the disease is frequently challenging to identify. It is frequently misdiagnosed as a fungal infection.MethodsWe report two cases of pythiosis, one was Pythium keratitis, the other was cutaneous pythiosis. The patient with corneal infection had no underlying disease, while the patient with cutaneous pythiosis had a history of liver cirrhosis, diabetes, and psoriasis. The corneal sample and subcutaneous pus were sent for metagenomic Next-Generation Sequencing (mNGS). To further diagnose the isolated strain, P. insidiosum zoospores were induced to produce by co-incubation with sterile grass leaves in sterile pond water. Their zoospores were used as an inoculum for drug susceptibility testing by disk diffusion and broth microdilution method.ResultsThe mNGS of two cases were reported as P. insidiosum. Zoospores were produced after incubation 48h. The zoospores were collected for drug susceptibility assay. All antifungal drugs, antibacterial drugs of β-Lactams, vancomycin, levofloxacin, ciprofloxacin, gentamicin, trimethoprim-sulfamethoxazole, clindamycin have no inhibitory activity against P. insidiosum in vitro. Minocycline, tigecycline, linezolid, erythromycin and azithromycin have significant in vitro activity against P. insidiosum. Based on the susceptibility results, the drug was changed from itraconazole to linezolid and minocycline, along with multiple debridements and drainage for cutaneous pythiosis. The patient was discharged after 24 days of treatment.ConclusionsEarly and accurate identification, combined with aggressive surgical debridement and appropriate drug therapy, can greatly improve patient managements. Conventional culture and zoospore induction remain gold standard for diagnosis; however, DNA-based method should be performed simultaneously. The drug susceptibility testing provides profound effects on proper drug selection against P. insidiosum.